Ödön von Horváth, Ein Sklavenball/ Pompej, Band 2 - Vejvar, Martin (Walter de Gruyter GmbH, 2015)
The farce Ein Sklavenball mit Gesang und Tanz [A Slave Ball with song and dance] and the comedy that was developed out of it Pompeji [Pompei] (both 1937) are the last two dramas completed by Ödön von Horváth. The present edition is the first to cover the immense wealth of source material on the genesis of both works. In addition, this edition puts especial emphasis on the intertextual traces left by Horváth's reading of the comedies of the Roman poet T. M. Plautus.